Are Prevalent Self-reported Cardiovascular Disorders Associated With Delayed Recovery From Whiplash-associated Disorders. Issue 3 (March 2015) - Palmlöf, Lina; Côté, Pierre; Holm, Lena W.; Carroll, Linda J.; Cassidy, J. David; Skillgate, Eva
<x xml:space="preserve">Abstract</x> Objectives: The aim of this cohort study was to investigate the association between self-reported cardiovascular disorders (CVD) and recovery from whiplash-associated disorder (WAD) after a traffic collision. Materials and Methods: This study was based on the Saskatchewan Government Insurance cohort, including individuals over 18 years of age, who made a traffic-injury claim or received health care after a traffic injury, between 1997 and 1999. Participants completed a baseline questionnaire and were followed up by telephone interviews at 6 weeks, 3 months, 6 months, 9 months, and 12 months after injury. Our sample includes a subcohort of 6011 participants who reported WAD (defined as answering "yes" to the question "Did the accident cause neck or shoulder pain") at baseline. The outcome, self-perceived recovery, was measured at all follow-up interviews. The presence of CVD and its effect on health was classified into 3 exposure categories: (1) CVD absent, (2) CVD present with no or mild effect on health, and (3) CVD present with moderate or severe effect on health. The association between CVD and recovery from WAD was assessed with Cox regression, and adjusted for potential confounders. Results: We found a crude association between comorbid CVD with moderate or severe effect on health in women. However, the adjusted association was weak and potentially affected by residual confounding. We found no association in men. Discussion: Our results suggest that CVD does not have an impact on the recovery of individuals with WAD.